Connexin 43 hemichannels and prostaglandin E2 release in anabolic function of the skeletal tissue to mechanical stimulation - Zhao, Dezhi; Wu, Jiawei; Acosta, Francisca M.; Xu, Huiyun; Jiang, Jean X. (Frontiers in Cell and Developmental Biology, 2023)
Bone adapts to changes in the physical environment by modulating remodeling through bone resorption and formation to maintain optimal bone mass. As the most abundant connexin subtype in bone tissue, connexin 43 (Cx43)-forming hemichannels are highly responsive to mechanical stimulation by permitting the exchange of small molecules (<1.2 kDa) between bone cells and the extracellular environment. Upon mechanical stimulation, Cx43 hemichannels facilitate the release of prostaglandins E2 (PGE2), a vital bone anabolic factor from osteocytes. Although most bone cells are involved in mechanosensing, osteocytes are the principal mechanosensitive cells, and PGE2 biosynthesis is greatly enhanced by mechanical stimulation. Mechanical stimulation-induced PGE2 released from osteocytic Cx43 hemichannels acts as autocrine effects that promote β-catenin nuclear accumulation, Cx43 expression, gap junction function, and protects osteocytes against glucocorticoid-induced osteoporosis in cultured osteocytes. In vivo, Cx43 hemichannels with PGE2 release promote bone formation and anabolism in response to mechanical loading. This review summarizes current in vitro and in vivo understanding of Cx43 hemichannels and extracellular PGE2 release, and their roles in bone function and mechanical responses. Cx43 hemichannels could be a significant potential new therapeutic target for treating bone loss and osteoporosis.